2013
DOI: 10.1093/annonc/mdt136
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of abiraterone acetate against metastatic castration-resistant prostate cancer progressing after docetaxel and enzalutamide (MDV3100)

Abstract: Abiraterone and prednisolone have modest antitumour activities in patients with mCRPC pretreated with docetaxel and enzalutamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
220
3
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(249 citation statements)
references
References 20 publications
14
220
3
12
Order By: Relevance
“…Cells were fixed with formaldehyde (3.7%), permeabilized using PBS (0.1% TRITON X-100), and incubated overnight possible mechanistic advantage of CYP17 inhibitors compared with that of pure antiandrogens (15). Studies have suggested that there is considerable cross-resistance to abiraterone in patients progressing on enzalutamide treatment, although a few patients did show decreases in their PSA levels (55,56). It will be informative in future studies to address whether these responders were due to abiraterone-inhibitory activity on AR mutants, such as F876L.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed with formaldehyde (3.7%), permeabilized using PBS (0.1% TRITON X-100), and incubated overnight possible mechanistic advantage of CYP17 inhibitors compared with that of pure antiandrogens (15). Studies have suggested that there is considerable cross-resistance to abiraterone in patients progressing on enzalutamide treatment, although a few patients did show decreases in their PSA levels (55,56). It will be informative in future studies to address whether these responders were due to abiraterone-inhibitory activity on AR mutants, such as F876L.…”
Section: Methodsmentioning
confidence: 99%
“…15 Small gains in a minority of patients were demonstrated when abiraterone was given following enzalutamide, albeit in two small cohorts where 25-29% of patients were Eastern Cooperative Oncology Group performance status 2. 16,17 In a series of 35 patients receiving enzalutamide following abiraterone and docetaxel, the median time to progression was just 4 months. 18 Results of ongoing trials are awaited; however, it is clear that predictive biomarkers are urgently needed to inform treatment sequencing, and understanding the mechanisms of resistance is key.…”
Section: Challenges and Remaining Questionsmentioning
confidence: 99%
“…Reportes iniciales parecen coincidir que las respuestas a AA post enzalutamida (o viceversa) son menores que al tratamiento primario [60][61][62][63] . Agregando mayor complejidad a la elección de tratamiento inicial, estudios preclínicos sugieren cierta superposición en los mecanismos de acción y por lo tanto, resistencia cruzada parcial entre taxanos y hormonoterapia [64][65] , fenómeno que sería menor en el caso de cabazitaxel 66 .…”
Section: Futuro: Secuenciación Y/o Sinergiaunclassified